MECANISMOS MOLECULARES NO HIRSUTISMO: EXPRESSÃO GÊNICA DE ENZIMAS DO METABOLISMO ANDROGÊNICO NO FOLÍCULO PILOSO E ASSOCIAÇÃO COM O DIAGNÓSTICO ETIOLÓGICO - Oliveira, Isabel; D’Avila, Angela; S Brum, Ilma; Spritzer, Poli Mara (Clinical and Biomedical Research, 2022)
Androgens are the main hormonal regulators of human hair growth and they are related to clinical conditions such as hirsutism. The aim of this study was to analyze the gene expression of androgen receptor (AR), type 1 and type 2 5a-reductase isoenzymes (5a R1 and 2) and type 2 17b hydroxysteroid dehydrogenase (17b-HSD 2) in plucked scalp hairs from hirsute patients and normal subjects. We studied 33 women with hirsutism [20 with polycystic ovary syndrome (PCOS), 13 with idiopathic hirsutism (IH)]; 15 control women; and 10 control men. Hirsutism was assessed by a modified Ferriman-Gallwey method. Hormonal status was assessed between days 2 and 10 of the menstrual cycle or on any day when the patients were amenorrheic. AR and enzymes mRNA levels were estimated by reverse transcriptionpolymerase chain reaction (RT-PCR). AR expression was similar in all groups. The gene expression of 5a R2 was not detected in any hair samples analyzed in this study. No differences were found on 5a R1 mRNA levels between men and normal women (0.78 ± 0.05 vs. 0.74 ± 0.06, respectively). 5a R1 gene expression in the plucked hair cells from scalp of normal women (0.85 ± 0.04), PCOS (0.78 ± 0.05) and IH (0.80 ± 0.06) was also similar. 17b-HSD2 gene expression in hirsute patients was lower (2.2±0.13 and 2.0±0.15, for PCOS and IH, respectively) than in normal women (3.1±0.17, p<0.05), and similar to men (1.8±0.22). In conclusion, these results indicate that there are no changes on 5a R1 gene expression in the plucked hair cells from scalp, related to gender or hirsutism. The lower expression of 17b-HSD2 mRNA in scalp hairs of hirsute patients suggests androgen metabolism disturbances with predominance of more potent androgens, as occurs in men.